Pengaruh Online Review Dan Virtual Reality Terhadap Attitude Toward Destination Dan Intention To Visit Destination - Stefanus Alvin Hartono; Sri Hartini (Fakultas Ekonomi Universitas Kadiri, 2021)
This study aims to validate the effect of online review and application of virtual reality on attitudes towards destinations and canceling intentions to visit destinations. The research approach uses quantitative data and data with survey methods. The sampling technique in this study used purposive sampling which is part of nonprobability sampling. The research sample is a consumer who is active in online activities and can use a website, with a minimum age of 19 years as many as 160 samples. The analysis technique used is anova analysis and regression. The results showed that online reviews and the application of virtual reality had a positive effect on attitudes towards destinations and intention to visit destinations. Then online positive and negative reviews have a significant effect on attitudes towards destinations and intention to visit destinations. Meanwhile, the application of virtual reality also has a significant effect on attitudes towards destinations and intention to visit destinations. This research also shows that the level attitude towards the purpose of visiting tourism can review and weaken the intention to visit the destination. With these results, the perceived attitude of tourist destinations towards tourism can assess or weaken the intention to visit tourist destinations